Alcohol consumption modulates prelimbic cortex response to cocaine following sequential cocaine and alcohol polysubstance use in the rat - Mesa, Javier R.; Carter, Emily; Padovan-Hernandez, Yasmin; Knackstedt, Lori A. (Frontiers in Pharmacology, 2023)
Polysubstance use (PSU), involves the consumption of more than one drug within a period of time and is prevalent among cocaine users. Ceftriaxone, a beta-lactam antibiotic, reliably attenuates reinstatement of cocaine seeking in pre-clinical models by restoring glutamate homeostasis following cocaine self-administration but fails to do so when rats consume both cocaine and alcohol (cocaine+alcohol PSU). We previously found that cocaine+alcohol PSU rats reinstate cocaine seeking similarly to cocaine-only rats, but demonstrate differences in reinstatement-induced c-Fos expression throughout the reward system, including a lack of change upon ceftriaxone treatment. Here, we used this model to determine if previous findings were caused by tolerance or sensitization to the pharmacological effects of cocaine. Male rats underwent intravenous cocaine self-administration immediately followed by 6 hours of home cage access to water or unsweetened alcohol for 12 days. Rats subsequently underwent 10 daily instrumental extinction sessions, during which time they were treated with either vehicle or ceftriaxone. Rats then received a non-contingent cocaine injection and were perfused for later immunohistochemical analysis of c-Fos expression in the reward neurocircuitry. c-Fos expression in the prelimbic cortex correlated with total alcohol intake in PSU rats. There were no effects of either ceftriaxone or PSU on c-Fos expression in the infralimbic cortex, nucleus accumbens core and shell, basolateral amygdala, or ventral tegmental area. These results support the idea that PSU and ceftriaxone alter the neurobiology underlying drug-seeking behavior in the absence of pharmacological tolerance or sensitization to cocaine.